Synthesis and biological activity of ferrocenyl furoyl derivatives. Issue 6 (3rd June 2017) - Tombul, Mustafa; Bulut, Adnan; Türk, Mustafa; Uçar, Büşra; Işılar, Özer
ABSTRACT: Due to the fact that ferrocene and furan derivatives have long been known to be one of the most biologically active compounds, preparation of their new derivatives might serve a very important purpose. Herein, five furoyl ferrocenes were synthesized via EA S reaction utilizing AlCl3 -EtAlCl2 Lewis acids. The compounds1–5 were obtained in moderate yields and characterized by IR, 1 H-NMR, 13 C-NMR, and mass spectrometry. Although toxicity increases with concentration, at 100 µg/mL concentration, the protection of cell viability was observed to be 70% level. At 50 µg/mL concentration, apoptosis in cancer cells observed was 63 ± 4% leading to high apoptosis ratio for the compound3 . For the compounds (1 –5 ), the necrotic effects were found to be between 21% and 39% at 50 µg/mL concentration.